Effect of acupuncture on TNF-alpha, IL-1b and IL-10 concentrations in the peritoneal exudates of carrageenan-induced peritonitis in rats - Scognamillo-szabó, Márcia Valéria Rizzo [UNESP]; Bechara, Gervásio Henrique [UNESP]; Cunha, Fernando De Queiroz (Universidade Federal de Santa Maria, 2005)
Acupuncture is an ancient and empirical therapeutic procedure known by its efficacy in the treatment of pain. However, the influence of acupuncture on inflammatory process is still poorly understood and additional research is needed. In this work, we investigated the mechanism of action of manual acupuncture on the inhibition of neutrophil migration to the peritoneal cavity induced by the inflammatory stimulus carrageenan in Wistar rats. Previous results from our laboratory showed that this anti-inflammatory effect is not due to endogenous corticoid release. Furthermore, the concentration of IL-1b, but not of TNF-alpha or IL-10 in the carrageenan-induced exudates was reduced in the acupuncture group. Further research will be needed to elucidate the mechanisms involved in the anti-inflammatory action of acupuncture as described here.

A acupuntura é método terapêutico milenar reconhecido por sua eficácia no tratamento da dor, porém seu efeito sobre processos inflamatórios é ainda pouco conhecido e maiores estudos são necessários. Neste trabalho, é investigado o mecanismo de ação da acupuntura manual sobre a inibição na migração de neutrófilos para a cavidade peritoneal induzida por carragenina em ratos Wistar. Resultados prévios indicam que esse efeito antiinflamatório não depende de hormônios corticóides. Entretanto, as concentrações de IL-1b no exsudato induzido por carragenina foram reduzidas pelo tratamento com acupuntura. Por outro lado os níveis de TNF-alfa e IL-10 não foram afetados pelo tratamento. Mais pesquisas poderão elucidar os mecanismos envolvidos na ação antiinflamatória da acupuntura.
Efeito da acupuntura sobre a concentração de TNF-alfa, IL-1b e IL-10 no exsudato peritoneal de ratos com peritonite induzida por carragenina
Keywords: acupuncture; inflammation; cytokines; neutrophils; rats; carrageenan; acupuntura; inflamação; citocinas; neutrófilos; ratos; carragenina